Implementation of digital voting system using blockchain - Sabbir, Naimul Hasan; Islam Chowdhury, Md. Amirul; Das, Rishikesh; Mukit, K.A. (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.